Assessing the development of intercultural sensitivity in business settings: how to interact successfully with people belonging to another nation - Ablonczy-Mihályka, Lívia (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2025)
With globalisation, many non-native English speakers do business in changeable and culturally diverse settings. The ability to communicate across cultures and understand diverse perspectives is a necessity in order to achieve a competitive advantage in our global economy.The research to be discussed in the paper is a part of a complex research conducted in 2013-2014, in Hungary. The paper focuses on demonstrating how culture influences behaviour in international settings where business partners have differing values, attitudes and norms. More than 200 Hungarian managers and professionals were asked to answer close-ended and open-ended questionsmaking choices among a set of alternatives focusing on their attitudes in several business situations.The data was collected with the aid of a research questionnaire and entered into the SPSS programme, then analysed using appropriate statistical methods.The findings reveal that companies seem to find it difficult to adapt their messages to suit different cultural groups but there are new approaches with promise the most success for communicating and working effectively in international business settings.